Pengaruh Pelayanan dan Variasi Produk terhadap Keputusan Pembelian Konsumen (Studi Kasus: Aiko Mart Sialang Atas, Kec. Kapur IX, Kab. Limapuluh Kota) - Maytri Chandani Putri; Habibatur Ridhah (ARZUSIN, 2026)
Service quality and product variety have received attention in several previous studies, but studies that specifically discuss the influence of these two variables on consumer purchase decisions in the context of local retail remain limited. This study aimed to analyze the influence of service quality and product variety on consumer purchase decisions at Aiko Mart Sialang Atas. This study used a quantitative approach with a survey design, involving 99 respondents selected using purposive sampling. Data were collected using a questionnaire and analyzed using multiple linear regression. The results showed that service quality had a significant effect on consumer purchase decisions, with a calculated t-value of 2.025 and a significance value of 0.046. Product variety also had a significant effect on purchase decisions, with a calculated t-value of 2.538 and a significance value of 0.013. Simultaneously, service quality and product variety had a significant effect on purchase decisions, with a calculated F-value of 5.186 and a significance value of 0.007. The coefficient of determination of 42.1% indicated that the two variables contributed to consumer purchase decisions, while the remainder was influenced by other variables outside this study. This finding contributes to the development of studies on consumer behavior and marketing management, particularly in the context of local retail businesses. Thus, service quality and product variety are important factors in improving consumer purchase decisions, so business actors need to strengthen service quality and product completeness as a more effective retail marketing strategy.